Halogen-containing thiazole orange analogues – new fluorogenic DNA stains - Vasilev, Aleksey A.; Kandinska, Meglena I.; Stoyanov, Stanimir S.; Yordanova, Stanislava B.; Sucunza, David; Vaquero, Juan J.; Castaño, Obis D.; Baluschev, Stanislav; Angelova, Silvia E. (Beilstein Journal of Organic Chemistry, 2017)
Novel asymmetric monomeric monomethine cyanine dyes 5a–d, which are analogues of the commercial dsDNA fluorescence binder thiazole orange (TO), have been synthesized. The synthesis was achieved by using a simple, efficient and environmetally benign synthetic procedure to obtain these cationic dyes in good to excellent yields. Interactions of the new derivatives of TO with dsDNA have been investigated by absorption and fluorescence spectroscopy. The longest wavelength absorption bands in the UV–vis spectra of the target compounds are in the range of 509–519 nm and these are characterized by high molar absorptivities (63000–91480 L·mol−1·cm−1). All investigated dyes from the series are either not fluorescent or their fluorescence is quite low, but they become strongly fluorescent after binding to dsDNA. The influence of the substituents attached to the chromophores was investigated by combination of spectroscopic (UV–vis and fluorescence spectroscopy) and theoretical (DFT and TDDFT calculations) methods.
Keywords: cyanine dyes; DFT calculations; green synthesis; nucleic acids; thiazole orange

(untitled) - Lee, L. G.; Chen, C.-H.; Chiu, L. A. (Cytometry, 1986)

U.S. Patent - Lee, L. G.; Chen, C.-H. (Detection of reticulocytes, RNA or DNA, 1989)

(untitled) - Kurutos, A.; Ryzhova, O.; Trusova, V.; Tarabara, U.; Gorbenko, G.; Gadjev, N.; Deligeorgiev, T. (Dyes Pigm., 2016)

(untitled) - Crnolatac, I.; Rogan, I.; Majić, B.; Tomić, S.; Deligeorgiev, T.; Horvat, G.; Makuc, D.; Plavec, J.; Pescitelli, G.; Piantanida, I. (Anal. Chim. Acta, 2016)

(untitled) - Carlsson, C.; Larsson, A.; Jonsson, M.; Albinsson, B.; Norden, B. (J. Phys. Chem., 1994)

(untitled) - Netzel, T. L.; Nafisi, K.; Zhao, M.; Lenhard, J. R.; Johnson, I. (J. Phys. Chem., 1995)

(untitled) - Karlsson, H. J.; Bergqvist, M. H.; Lincoln, P.; Westman, G. (Bioorg. Med. Chem., 2004)

(untitled) - Nygren, J.; Svanvik, N.; Kubista, M. (Biopolymers, 1998)

(untitled) - Wang, Y.; Yang, J.; Wu, X.; Li, L.; Sun, S.; Su, B.; Zhao, Z. (Anal. Lett., 2003)

(untitled) - Patonay, G.; Salon, J.; Sowell, J.; Strekowski, L. (Molecules, 2004)

(untitled) - Bohländer, P. R.; Wagenknecht, H.-A. (Methods Appl. Fluoresc., 2015)

(untitled) - Zhang, X. H.; Liu, Q.; Shi, H. J.; Wang, L. Y.; Fu, Y. L.; Wei, X. C.; Yang, L. F. (Dyes Pigm., 2014)

(untitled) - Hirons, G. T.; Fawcett, J. J.; Crissman, H. A. (Cytometry, 1994)

(untitled) - Yan, X.; Grace, W. K.; Yoshida, T. M.; Habbersett, R. C.; Velappan, N.; Jett, J. H.; Keller, R. A.; Marrone, B. L. (Anal. Chem., 1999)

U.S. Patent - Hammond, M. L.; Jett, J. H.; Keller, R. A.; Marrone, B. L.; Martin, J. C. (DNA fragment sizing and sorting by laser-induced fluorescence, 1996)

(untitled) - Svanvik, N.; Westman, G.; Wang, D.; Kubista, M. (Anal. Biochem., 2000)

(untitled) - Ishiguro, T.; Saitoh, J.; Yawata, H.; Otsuka, M.; Inoue, T.; Sugiura, Y. (Nucleic Acids Res., 1996)

(untitled) - Bethge, L.; Jarikote, D. V.; Seitz, O. (Bioorg. Med. Chem., 2008)

XIVth Symposium on Chemistry of Nucleic Acid Components - Bethge, L.; Seitz, O. (2008)

(untitled) - Hövelmann, F.; Gaspar, I.; Ephrussi, A.; Seitz, O. (J. Am. Chem. Soc., 2013)

(untitled) - Hövelmann, F.; Seitz, O. (Acc. Chem. Res., 2016)

(untitled) - Arndt, S.; Walter, H.-K.; Wagenknecht, H.-A. (J. Visualized Exp., 2016)

(untitled) - Berndl, S.; Dimitrov, S. D.; Menacher, F.; Fiebig, T.; Wagenknecht, H.-A. (Chem. – Eur. J., 2016)

(untitled) - Gurrieri, S.; Wells, K. S.; Johnson, I. D.; Bustamante, C. (Anal. Biochem., 1997)

(untitled) - Nyberg, L.; Persson, F.; Åckerman, B.; Westerlund, F. (Nucleic Acids Res., 2013)

(untitled) - Tang, W.; Zhou, H.; Li, W. (PLoS One, 2015)

Real-Time PCR in Microbiology: From Diagnosis to Characterization - Mackay, I. M.; Mackay, J. F.; Nissen, M. D.; Sloots, T. P. (Caister Academic Press, 2007)

(untitled) - Bengtsson, M.; Karlsson, H. J.; Westman, G.; Kubista, M. (Nucleic Acids Res., 2003)

(untitled) - Carreon, J. R.; Mahon, K. P., Jr; Kelley, S. O. (Org. Lett., 2004)

(untitled) - Babendure, J.; Liddell, P. A.; Bash, R.; LoVullo, D.; Schiefer, T. K.; Williams, M.; Daniel, D. C.; Thompson, M.; Taguchi, A. K. W.; Lohr, D.; Woodbury, N. W. (Anal. Biochem., 2003)

(untitled) - Svanvik, N.; Nygren, J.; Westman, G.; Kubista, M. (J. Am. Chem. Soc., 2001)

Modified Nucleic Acids - Okamoto, A. (Springer International Publishing, 2016)

(untitled) - Wang, X.; Krull, U. J. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Wang, X.; Krull, U. J. (Anal. Chim. Acta, 2002)

(untitled) - Algar, W. R.; Massey, M.; Krull, U. J. (J. Fluoresc., 2006)

(untitled) - Steinmeyer, J.; Rönicke, F.; Schepers, U.; Wagenknecht, H.-A. (ChemistryOpen, 2017)

WO Patent - Ji, H. P.; Lau, B. T. C.; Miotke, L. (Quantification of mutant alleles and copy number variation using digital pcr with nonspecific dna-binding dyes, 2015)

(untitled) - Doan, P. H.; Pitter, D. R. G.; Kocher, A.; Wilson, J. N.; Goodson, T., III (J. Am. Chem. Soc., 2015)

(untitled) - Crnolatac, I.; Tumir, L.-M.; Lesev, N. Y.; Vasilev, A. A.; Deligeorgiev, T. G.; Mišković, K.; Glavaš-Obrovac, L.; Vugrek, O.; Piantanida, I. (ChemMedChem, 2013)

(untitled) - Zarkov, A.; Vasilev, A.; Deligeorgiev, T.; Stoynov, S.; Nedelcheva-Veleva, M. (Mol. Imaging, 2013)

(untitled) - Vasilev, A.; Lesev, N.; Dimitrova, S.; Nedelcheva-Veleva, M.; Stoynov, S.; Angelova, S. (Color. Technol., 2015)

(untitled) - Renikuntla, B. R.; Rose, H. C.; Eldo, J.; Waggoner, A. S.; Armitage, B. A. (Org. Lett., 2004)

(untitled) - Silva, G. L.; Ediz, V.; Yaron, D.; Armitage, B. A. (J. Am. Chem. Soc., 2007)

(untitled) - Brooker, L. G. S.; Keyes, G. H.; Williams, W. W. (J. Am. Chem. Soc., 1942)

(untitled) - Beilenson, B.; Hamer, F. M. (J. Chem. Soc., 1939)

(untitled) - Sexton, W. A. (J. Chem. Soc., 1939)

Green Chemistry: Theory and Practice - Anastas, P. T.; Warner, J. (Oxford University Press, 1998)

Green Chemistry: Frontiers in Benign Chemical Synthesis and Processes - Anastas, P. T.; Williamson, T. C. (Oxford University Press, 1998)

(untitled) - Anastas, P. T.; Kirchhoff, M. M. (Acc. Chem. Res., 2002)

(untitled) - Deligeorgiev, T.; Vasilev, A.; Tsvetkova, T.; Drexhage, K.-H. (Dyes Pigm., 2007)

(untitled) - Vasilev, A.; Deligeorgiev, T.; Kaloyanova, S.; Stoyanov, S.; Maximova, V.; Vaquero, J. J.; Alvarez-Builla, J. (Color. Technol., 2011)

(untitled) - West, W.; Pearce, S. (J. Phys. Chem., 1965)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B: Condens. Matter Mater. Phys., 1988)

(untitled) - Hehre, W. J.; Ditchfield, R.; Pople, J. A. (J. Chem. Phys., 1972)

(untitled) - Clark, T.; Chandrasekhar, J.; Spitznagel, G. W.; Von Ragué Schleyer, P. (J. Comput. Chem., 1983)

(untitled) - Frisch, M. J.; Pople, J. A.; Binkley, J. S. (J. Chem. Phys., 1984)

(untitled) - Igel-Mann, G.; Stoll, H.; Preuss, H. (Mol. Phys., 1988)

(untitled) - Tomasi, J.; Mennucci, B.; Cammi, R. (Chem. Rev., 2005)

Gaussian 09, Revision D.01 (Gaussian, Inc., 2009)

PyMOL, Version 1.8 (Schrödinger, LLC)

(untitled) - Deligeorgiev, T.; Vasilev, A.; Drexhage, K.-H. (Dyes Pigm., 2007)